(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Sliding contacts are widely used in electrical machines despite the trend towards non-contact methods of the electrical current transfer. In some cases, using of brush-contact devices is indispensable due to low cost and continuity of operations. One of methods to improve reliability of sliding contact is simulation modeling. This approach can significantly reduce the amount of expensive practical experiments in the study of different contact pairs characteristics. The paper introduces and describes a few new algorithms for simulation model of sliding contact which allow to improve precision and take into account more physical processes occurring in contact transient layer.